A cross‐country comparison on the use of blended learning in property education. Issue 2 (2014) - Joanna Poon
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to compare the use of blended learning in property education courses in different countries. The rationale for this study is to fill the research gap in this area. The focus of previous research on blended learning has been on individual countries only, and there is yet to appear any research on a cross‐country comparison. The purpose of this study is to identity the differences as well as the good practices using blended learning as a delivery approach in different countries As a result, individual countries can learn experience from another country. It is expected academics interested in using blended learning as a delivery approach will benefit from the research findings of this paper, through gaining an understanding of the advantages and challenges of using blended learning in different countries. Design/methodology/approach – This paper presents the research findings of questionnaire surveys and interviews with academics teaching property courses in Australia and the UK. The questionnaire aimed to gather academics' views on blended learning, their reasons for using blended learning as a teaching method, their design of blended learning courses and the support they provide to students on dealing with web technology. The aim of the interviews was to gain deeper insight into the successful factors and challenges in the use of blended learning. In total, 16 interviews were conducted. The interviews were recorded, transcribed and coded to identify similar themes. Content analysis was used as a method to analyse the interview data. The frequency of the answer in the questionnaire and comments from interviewees is presented. Findings – The Australian and UK property academics have similar views on many aspects of blended learning. Their definitions of blended learning are similar as their reasons to use it as a teaching method. The commonly used teaching and learning activities in their blended learning courses in both countries are, again, similar, such as the use of lectures, case studies and guest lecturers. On the other hand, the academics in the two countries face different challenges. A challenge faced by the Australian property academics is to deliver online courses to students who have limited internet downloading capacity and broadband width. Australia is a very large country and has more regional and remote areas. Another challenge faced by the Australian academics is keeping up with the constant introduction of new teaching and learning technology by their universities. On the other hand, the UK academics faced a different challenge, which was to sufficiently engage and encourage students to contribute in online Discussion Boards. The finding is possibly because the UK study was conducted two years prior to the Australian study and the idea of online discussions was relatively new to students at the time. The conclusion drawn from this research is that "time" and the size of the country influence the use of blended learning. Originality/value – This project is the first to conduct a cross‐country comparison on the use of blended learning in professionally accredited property courses.